PENGARUH BAURAN PRODUK DAN STRATEGI PROMOSI TERHADAP MINAT BELI KONSUMEN PADA CV. MAJU BERSAMA PEKANBARU - Ninda Agustiani; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this study was to determine the effect of product mix and promotional strategies on consumer purchase interest at CV. Maju Bersama Pekanbaru partially and simultaneously. In this research, the method used is quantitative descriptive analysis with the SPSS program. The population in this study are all consumers who purchase a car at CV. Maju Bersama Pekanbaru in the last year, namely 2020, totaled 257 people. Where the samples in this research are consumers of CV. Maju Bersama Pekanbaru, as many as 60 respondents. The results of this study indicate that the results of the product mix has a significant effect on consumer purchase interest. Second, that promotional strategies has a significant effect on consumer purchase interest. The results of the f-test the product mix and promotional strategies simultaneously have a significant effect on consumer purchase interest at CV. Maju Bersama Pekanbaru. Key Words: Product Mix, Promotional Strategies, Consumer Purchase Interest